2022
DOI: 10.1097/md.0000000000028785
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of primary pleural angiosarcoma

Abstract: Primary pleural angiosarcoma (PPA) is an extremely rare malignancy for which there is no consensus on treatment. The clinical course of PPA is usually quickly fatal, regardless of the treatment used.We summarized and evaluated a relatively large population of published PPA cases to assess prognostic factors, diagnostic approaches, treatment methods and clinical outcomes. Using the CNKI, Embase, and PubMed databases, literature published in English and Chinese from 1988 through 2020 was searched using the terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Primary pleural EAS is an extremely rare malignancy with atypical clinical symptoms and CT findings, resulting in a high rate of misdiagnosis. Wang et al [ 5 ] summarized 43 cases of primary pleural angiosarcoma with a mean age of 64 years (24–87 years) which indicated a higher incidence in males. The most frequent manifestations were pleural mass (44%) and pleural invasion (70%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary pleural EAS is an extremely rare malignancy with atypical clinical symptoms and CT findings, resulting in a high rate of misdiagnosis. Wang et al [ 5 ] summarized 43 cases of primary pleural angiosarcoma with a mean age of 64 years (24–87 years) which indicated a higher incidence in males. The most frequent manifestations were pleural mass (44%) and pleural invasion (70%).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no standard therapy. Pleural effusion and hemothorax were significant predictors of decreased survival [ 5 ]. The mean survival after the diagnosis was less than 1 year [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, complete surgical resection is the first and optimal method for the treatment of angiosarcomas. A study 22 reported that patients who undergo surgical resection survive for at least 15 years. Angiosarcomas are invasive and prone to metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Some thyroid carcinomas also can be both HEG1 and claudin‐4‐positive 3,9 . One potential positive HEG1/negative claudin‐4 confounder is angiosarcoma, but these tumours are extremely rare in the serosal membranes; a recent review of the literature from 1988 to 2020 found only 43 primary pleural angiosarcomas, 20 and most angiosarcomas are not epithelioid 21 . For comparison there are approximately 3000 mesotheliomas every year in the United States alone and 34 000 worldwide 22 …”
Section: Conclusion and Hypothesismentioning
confidence: 99%